(untitled) (The International Journal for Scientific Research, 2023)
Introduction: Nosocomial infections can have significant negative consequences, including extra hospitalization days, additional costs, and even deaths, depending on the site of infection. These consequences and associated costs can be substantial, and it is important to identify patients at highest risk for infection in order to prioritize prevention and control efforts. In this review, we aimed to include all preventive, control and surveillance strategies targeting nosocomial infections. Methods: A systematic review was conducted to examine the effects of modifications to hospital architecture on nosocomial infections in intensive care units (ICUs), surgical departments, isolation units, and hospitals in general. The review included experimental and nonexperimental studies published before 2022 in English. The search was conducted using a combination of keywords and abbreviated terms related to hospital architecture and nosocomial infections, and was carried out through seven medical databases, reference lists, and expert consultation. In addition, the Cochrane Controlled Trials Database and the internet were checked. The bibliographies of reviewed papers, reports, and textbooks were searched by hand and experts in the field of hospital hygiene were consulted. The principal outcome measure was the rate of nosocomial infections. Results: The search identified 178 articles that met the inclusion criteria, but only 17 of these described completed concurrent or historical cohort studies that matched the criteria. Most of the articles were categorized at the lowest level of evidence and did not include a meta-analysis, systematic review, or randomized controlled trial. The interventions in hospital architecture generally resulted in more space per hospital bed, single rooms, or easily accessible handwashing facilities. Of the 17 included studies, three documented a statistically significant decrease in nosocomial infection after the intervention. However, none of the studies addressed other types of nosocomial infection, such as postoperative pneumonia or urinary tract infection. Conclusions: To effectively control these infections, healthcare institutions should implement infection control programs and use appropriate antimicrobials, including prophylactic use when appropriate. Efficient surveillance methods, including data collection from multiple sources and regular evaluation and maintenance, are also important for effectively implementing interventions and maintaining the effectiveness of surveillance systems.